A Review of Monitoring Construction Equipment in Support of Construction Project Management - Nakanishi, Yutaro; Kaneta, Takashi; Nishino, Sayaka (Frontiers in Built Environment, 2022)
Progress monitoring is an important aspect of construction project control that is fundamental to proper project management and decision-making. Traditional monitoring methods are inaccurate, time-consuming, and labor-intensive because they rely on large-scale manual operations. The defect of the method has been identified as one of the major problems causing project delays and cost overruns. In recent years, a variety of emerging automated data collection, analysis, and visualization techniques have been used to establish methods for digitized, real-time progress monitoring, and there are several papers that address these methodologies and comprehensive reviews. Among them, the authors conducted a review of various studies focusing on how to apply the monitoring of construction equipment to project management. The authors selected the studies of interest using research databases such as Google Scholar and ScienceDirect. Then, the authors classified those studies by technology, purpose, and subject matter, and analyzed the details. Through a literature review, it was revealed that most of the studies were focused on digitalization and review of the lifted path for safety improvement, and few studies were conducted for progress management, such as collection and analysis of work results. In addition, the authors revealed that several studies use the combination of existing technologies with new modeling technologies such as BIM (Building Information Modeling). It was also clarified that the technology applied to the monitoring is not even one, but a combination of multiple technologies to achieve each objective. Furthermore, even in the case of monitoring construction equipment, the authors found that workers, construction materials, and even the activity itself are also monitored as well as construction equipment.